(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
In today’s educational environment, medical students face a heavy academic workload, a significant amount of theoretical material, and constant psycho-emotional stress. This often leads to decreased physical activity, deterioration in overall health, development of chronic fatigue, and an increased risk of various diseases. This article examines the role of physical activity as a key factor in maintaining the health of medical students. Particular attention is paid to analyzing the impact of regular physical activity on the body’s functional state, performance, and stress resilience. This article examines such types of physical activity as aerobic exercise, strength training, and active recreation, as well as their impact on the cardiovascular, respiratory, and nervous systems. It emphasizes that moderate and systematic physical activity contributes to improved cognitive function, increased concentration, and academic performance. The paper also analyzes the main causes of insufficient student physical activity, including time constraints, intense study schedules, lack of motivation, and a lack of accessible sports infrastructure. There is evidence that regular physical exercise helps reduce anxiety levels, prevent stress, and promote a healthy lifestyle.